2005
DOI: 10.4049/jimmunol.174.1.498
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-Boswellic Acids Inhibit Lipopolysaccharide-Mediated TNF-α Induction in Monocytes by Direct Interaction with IκB Kinases

Abstract: Expression of proinflammatory cytokines by monocytes is tightly regulated by transcription factors such as NF-κB. In this study, we show that, in LPS-stimulated human peripheral monocytes, the pentacyclic triterpenes acetyl-α-boswellic acid (AαBA) and acetyl-11-keto-β-boswellic acid (AKβBA) down-regulate the TNF-α expression. AαBA and AKβBA inhibited NF-κB signaling both in LPS-stimulated monocytes as detected by EMSA, as well as in a NF-κB-dependent luciferase gene reporter assay. By contrast, the luciferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(135 citation statements)
references
References 57 publications
2
129
1
1
Order By: Relevance
“…55 Accordingly, it is speculated that BAs may exert their anti-inflammatory effect mainly by inhibiting the release of proinflammatory LT products from leukocytes and platelets 55 and by the inhibition of NF-κβ and subsequent downregulation of TNF-α expression in activated monocytes. 56 The protective effect of Boswellia against RIR is not attributed to the modulation of oxidative stress as it does not affect serum MDA or renal SOD levels. But it may block its subsequent inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…55 Accordingly, it is speculated that BAs may exert their anti-inflammatory effect mainly by inhibiting the release of proinflammatory LT products from leukocytes and platelets 55 and by the inhibition of NF-κβ and subsequent downregulation of TNF-α expression in activated monocytes. 56 The protective effect of Boswellia against RIR is not attributed to the modulation of oxidative stress as it does not affect serum MDA or renal SOD levels. But it may block its subsequent inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of cathepsin G may also explain the slight but still significant reduction of oedema formation and cell infiltration upon pretreatment with Ab-BA, which was the least potent inhibitor of mPGES1 and failed to suppress PGE2 formation in whole blood. Similarly, interference with other pro-inflammatory components, such as cytokines and transcription factors (Syrovets et al, 2005;Kunnumakkara et al, 2009), may suppress COX-2 induction, explaining the reduced 6-keto PGF 1a levels in the exudates of KBA-and Ab-BA-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Pilot clinical studies have suggested some efficacy of frankincense preparations in the treatment of osteoarthritis (OA), rheumatoid arthritis (RA), inflammatory bowel diseases, asthma and cancer (see Ammon, 2006;Poeckel and Werz, 2006). Molecular mechanisms responsible for these therapeutics effects have been mainly attributed to the interference of 3-O-acetyl-11-keto-b-BA (AKBA) with signalling pathways including the nuclear factor-kB route (Syrovets et al, 2005), mitogen-activated protein kinase pathway and Ca 2+ signalling (Poeckel et al, 2006a) as well as targeting human leukocyte elastase (HLE) (Safayhi et al, 1997), 5-lipoxygenase (5-LOX) (Safayhi et al, 1992), platelet-type 12-lipoxygenase (12S-LOX) (Poeckel et al, 2006b) and COX-1 . However, in vivo studies confirming the pharmacological relevance of these proposed target interactions are still missing, and the efficacy of defined BAs in in vivo models of inflammation remains to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that AKBA potentiated apoptosis induced by TNF-a and chemotherapeutic agents, inhibited TNF-a-induced cell invasion, and abrogated RANKL-induced osteoclastogenesis through inhibition of NF-jB activation. AKBA inhibited lipopolysaccharide induced production of TNF-a in monocytes was mediated by suppression of IjBa kinases [72]. In vivo treatment with AKBA inhibited the growth and metastasis of colorectal cancer in orthotopically implanted tumors in nude mice.…”
Section: Boswellic Acidmentioning
confidence: 99%